A study on undergraduates' preferences between CHAHGPT vs GOOGLE in the learning environments - Cheng, Grace Chi Sze (2024)
As technology continues to shape educational environments, it is critical to understand undergraduate students' preferences for learning tools. This study explored undergraduate students' preferences for using ChatGPT and Google in their learning environments and their role in the undergraduate learning environment. The study used a quantitative methodology, and 50 questionnaires were distributed to undergraduate students between the ages of 18 and 26. Using Uses and Gratification Theory (UGT) as a theoretical framework, we used descriptive and cross-tabulation analysis to explore students' preferences for ChatGPT and Google and their impact on undergraduate learning outcomes. The study found that undergraduate students, especially males, preferred ChatGPT for its quick response and creativity. With a balanced preference among females, Google was favoured for search accuracy and voice search. Students used Google for research and study, while they found ChatGPT helpful in writing papers and understanding lectures. Most undergraduates are open to AI tools in education for improved learning and access to information. The study concluded that both ChatGPT and Google have unique strengths and that undergraduate students would choose the right tool for their specific needs. Future educational strategies should consider the effective integration of both tools to maximise their academic potential and better support student learning and development.